Family cognitive remediation therapy for anorexia nervosa. (April 2015) - Lask, Bryan; Roberts, Alice
Anorexia nervosa (AN) in childhood and adolescence has a poor prognosis. It is possible that this may in part be due to the fact that cognitive weaknesses that appear to be risk factors for its development and maintenance are not being targeted in treatment. Through its focus on these deficits, cognitive remediation therapy (CRT) has been shown to be a promising intervention for AN. Furthermore, family interventions are widely recommended for this patient population, but to date no studies have reported the use of CRT in a family setting. This paper presents a case series in which family-based CRT was a significant component of the management. It was well received by patients and their families and previously treatment resistant patients became more engaged with the entire treatment process. In addition, all patients receiving family-based CRT went on to make progress towards recovery. These initial clinical observations suggest family-based CRT is likely to be a useful addition to treatment for child and adolescent AN and justifies formal evaluation.